(untitled) - Barenblatt, Griory Isaakovich (Cambridge, 2003)
This book describes and teaches the art of discovering scaling laws, starting from dimensional analysis and physical similarity, which are given a modern treatment here
Keywords: Scaling laws (Statistical physics),discovering scaling laws; Khám phá quy luật mở rộng,Thống kê vật lý